Unwilling the Smartphone Addiction, Fear of Missing Out and Mental Health Issues in Youth (Journal of Asian Development Studies, 2024)
The focus of present is to explore the relationship between smartphone addiction, fear of missing out and mental health issues in youth. Understanding how specific worries of missing out and mental health issues contribute to the development and exacerbation of smartphone addiction can provide valuable insights for prevention strategies. For this purpose, the sample for the current study was calculated by the G power formula (F, t, χ2, z, and exact tests) and 200 participants were selected through convenient sampling. A correlational research design was used. A short smartphone addiction scale (Kwon et al., 2013), fear of missing out (Przybylski et al., 2013) and mental health questionnaire scale (Houston) were used to measure the study variables. Results of the correlation analysis revealed that there is a significant positive relationship between smartphone addiction, fear of missing out and mental health issues in youth. Further results demonstrate that smartphone addiction significantly predicts mental health issues in youth. However, results showed that there are no gender differences in smartphone addiction, Fear of missing out and mental health issues among young adults. The current study findings are beneficial for youth to understand how smartphone addiction is linked to fear of missing out and mental health issues and what steps should be taken to reduce these issues in youth. To conclude, the present research study highlights the need for awareness and intervention strategies to mitigate the adverse effects of Smartphone addiction and FOMO on mental health, emphasizing the importance of digital literacy and balanced technology use among youth.